PENGARUH TEGANGAN TABUNG (KV) TERHADAP KUALITAS CITRA RADIOGRAFI PESAWAT SINAR-X DIGITAL RADIOGRAPHY (DR) PADA PHANTOM ABDOMEN - Sriwahyuni Sriwahyuni (Spektra: Jurnal Fisika dan Aplikasinya, 2017)
The measurement of image quality ofÃ‚ Digital Radiography (DR) with using the abdomen phantom. Image take with low kV to high kV for 10 times exposure. Image processing is done using the image application. The resulting radiograph image is analyzed by FFT analysis, Histogram and Gaussian Filter. In the FFT analysis the radiographic image tends to differ according to the tube voltage variation of 40 kV to 85 kV. In the radiographic image histogram analysis, including the imperfect image category because the distribution of pixel distribution is not yet complete in the gray scale area for all exposure variations. In the analysis using Gaussian filters the resulting radiographic image tends to be the same so that although using low kV and high kV the image will be the same. The use of Gaussian filters can help reduce the use of high kV on abdominal examination and reduce exposure to radiation dose. Keywords: Digital Radiography, Image Quality, Fourier Transform Filter, Gaussian Filter, Histogram.